The Effect of Financial Performance on the Stock Price of Service Companies Listed on the Indonesia Stock Exchange (IDX) - Rasyid, Abdul; Zakaria, Z. (Manunggal Halim Jaya, 2023)
This study aims to determine the financial performance of PT. Wijaya Karya Beton Tbk based on the analysis method of liquidity ratio, profitability ratio and solvency ratio for the period 2019-2022. The data collection technique used is documentation, with documents in the form of company financial statements in 2019-2022. Data analysis techniques use case study techniques to obtain data as material in the preparation of research. As for analyzing the development of financial performance, this study uses descriptive analysis techniques where the data obtained in the field is processed in such a way as to provide systematic, factual, and accurate data on the problems to be studied. The results showed that the company's financial performance assessment based on the analysis of liquidity ratios, solvency ratios and profitability ratios for the period 2019-2022, with details, namely (a) financial performance based on liquidity ratios has fluctuated in the last 4 years (2019-2022) this is due to the increasing number of current assets and current debt from year to year. (b) Financial performance based on Profitability Ratio has decreased in the last year (2019-2022). This is due to the increasing amount of profit after tax. (c) Financial performance based on Solvency Ratio has decreased in the last year (2019-2022) this is due to the increase in total assets.